Analyzing Difficulties in Problem Solving of the Polygon Area for Elementary Students - AHMAD NIZAR RANGKUTI (Universitas Jambi, Indonesia, 2019)
Mathematics is part from a human activity; it cannot be separated from daily human life, both in theory and in practice. Problem solving is the most important topic in learning Mathematics. However, problem solving is a complex process that has many components. One of them is the difficulty of students in answering the questions about how to find the area of polygon. Students are hard to find out two or more shapes contained in polygon. The students are hard to find unknown measurements, because they do not understand the questions. Therefore, teachers should give guidance to the students in order to help them to solve problems correctly. The purpose of this study was to analyze students’ difficulties to solve the problems of the polygon area questions for the fourth grade of one state elementary in Padang Sidimpuan City. There were 33 participants consisting of 16 male and 17 female students. The students were given a problem solving test and the questions were related to a wide area of polygon consisting of five questions. The findings of the study indicated that students were hard to find solutions to solve mathematical problems of the polygon area flat shapes in class, suggesting that teachers should strive to develop students’ critical thinking as well as creative thinking so they will have a good problem solving skills.